Much more than just another guidance document. (28th October 2016) - Kulkarni, K.
Abstract : Summary: As a pediatric hematologist oncologist with clinical and research interests in thrombosis in high‐risk pediatric populations, and also as a member of the ISTH Early Career Task Force, I had the opportunity to develop a guidance document on 'Thromboprophylaxis for central venous catheters in the pediatric population' for the 'Guidelines and Guidance Documents' committee. In this communication, I share my experiences to date; I discuss my excitement and initial success, the steep learning curve required to build research acumen, the lessons learnt, and the opportunities and challenges faced. My experience with preparing the guidance document was much more than writing 'just another guidance document'.